Prevalence of pelvic floor dysfunction, bother, and risk factors and knowledge of the pelvic floor muscles in norwegian male and female powerlifters and olympic weightlifters - Skaug, K. L.; Engh, M. E.; Frawley, H.; Bø, K. (The Journal of Strength and Conditioning Research, 2022)
Strenuous exercise has been suggested as a risk factor of pelvic floor dysfunction (PFD). Powerlifters and Olympic weightlifters compete with high external loads. To date, knowledge of PFD in these athletes has been sparse. The aim of this study was to investigate prevalence, risk factors, and bother of PFD in powerlifters and Olympic weightlifters and their knowledge of the pelvic floor muscles (PFM). All athletes aged =18 years competing in =1 National Championship in powerlifting or Olympic weightlifting in 2018/2019 were invited. The International Consensus on Incontinence Questionnaires were used to assess PFD. One hundred eighty women and 204 men participated. The prevalence of urinary incontinence (UI), anal incontinence (AI), and pelvic organ prolapse in women was 50.0, 80.0, and 23.3%, respectively. Stress UI (SUI) was reported by 41.7% of the women and 87.8% reported a negative influence on sport performance. The prevalence of UI and AI in men was 9.3 and 61.8%. In women, increasing body mass index was significantly associated with SUI (odds ratio [OR]: 1.09, 95% confidence interval [CI]: 1.01-1.17) and international level of competition (OR: 3.27, 95% CI: 1.32-8.07) and weightlifting =4 d·wk-1 (OR: 0.26, 95% CI: 0.08-0.86) with AI. In men, increasing age (OR: 1.03, 95% CI: 1.00-1.07) and frequently straining to void (OR: 4.84, 95% CI: 1.02-22.94) were significantly associated with AI. Forty-three percent of the women and 74% of the men did not know why and 44.4 and 72.5% how to train the PFM. In conclusion, the prevalence of PFD was high, and the athletes had limited knowledge of the PFM.